Impact of Taurine in OVO Injection on Hatchability, Intestinal Development, and Biochemical Parameters of Newly Hatched Broiler Chicks - Ali H. Al-obaidy; Mohamed M. Alalkawy; Ahmed A. Al-Hadidi; Mohammed H. Al-saady; Tamara A. Al-Samarai; Alaq A. Awade (مجلة ديالى للعلوم الزراعية)
This experiment was conducted to study the effects of taurine in ovo injection on hatchability, chick quality, intestinal development, and biochemical parameters of broiler chick Ross 308, On 18th day of incubation, 1050 fertilized hatching eggs randomly distributed into seven treatments with 150 eggs for each treatment, T1 without injection (negative control), T2 control with injection of 0.2 ml normal saline /egg (carrier control), and T3–T7 (injected with 0.2 mL normal saline containing 50, 100, 150, 200, and 250 mg taurine per egg, respectively). Statistical analysis showed a significant effect of taurine injection on hatchability (P=0.000) and mortality (P=0.005), Treatments T3 and T4 recorded the highest hatchability and the lowest mortality. Additionally, treatment T3 showed significant improvement (P=0.000) in body weight, with a mean of 44.51 g, followed by treatment T4 with a mean weight of 43.03 g, compared to 40.06 and 40.75 g in T1 and T2, respectively. Similarly, chick length was significantly greater (P=0.000) in T3 (22.77 cm) and T4 (22.50 cm) compared to T1 (21.85 cm) and T2 (21.70 cm) .T3 and T4 led to a significant increase in total protein (P=0.001), globulin (P=0.006), and high - density lipoprotein (P=0.001) concentrations and a significant decrease in cholesterol (P=0.000), triglycerides(P=0.001), and liver enzyme concentrations, It can be concluded that In ovo injection with 50 mg/egg of taurine, improved hatchability, productivity, and physiological traits of broiler chicks.